Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Given
f
(
x
)
=
2
x
2
−
7
x
−
18
f(x)=2 x^{2}-7 x-18
f
(
x
)
=
2
x
2
−
7
x
−
18
, find
f
(
−
1
)
f(-1)
f
(
−
1
)
\newline
Answer:
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate expression when a complex numbers and a variable term is given
Full solution
Q.
Given
f
(
x
)
=
2
x
2
−
7
x
−
18
f(x)=2 x^{2}-7 x-18
f
(
x
)
=
2
x
2
−
7
x
−
18
, find
f
(
−
1
)
f(-1)
f
(
−
1
)
\newline
Answer:
Substitute
x
x
x
with
−
1
-1
−
1
:
To find
f
(
−
1
)
f(-1)
f
(
−
1
)
, we need to substitute
x
x
x
with
−
1
-1
−
1
in the function
f
(
x
)
=
2
x
2
−
7
x
−
18
f(x) = 2x^2 - 7x - 18
f
(
x
)
=
2
x
2
−
7
x
−
18
.
Calculate square of
−
1
-1
−
1
:
Substitute
x
x
x
with
−
1
-1
−
1
:
f
(
−
1
)
=
2
(
−
1
)
2
−
7
(
−
1
)
−
18
f(-1) = 2(-1)^2 - 7(-1) - 18
f
(
−
1
)
=
2
(
−
1
)
2
−
7
(
−
1
)
−
18
.
Multiply by
2
2
2
:
Calculate the square of
−
1
-1
−
1
:
(
−
1
)
2
=
1
(-1)^2 = 1
(
−
1
)
2
=
1
.
Multiply
−
7
-7
−
7
by
−
1
-1
−
1
:
Multiply
2
2
2
by the square of
−
1
-1
−
1
:
2
×
1
=
2
2 \times 1 = 2
2
×
1
=
2
.
Add and subtract
18
18
18
:
Multiply
−
7
-7
−
7
by
−
1
-1
−
1
:
−
7
×
−
1
=
7
-7 \times -1 = 7
−
7
×
−
1
=
7
.
Calculate final value:
Add the results of the previous steps and subtract
18
18
18
:
f
(
−
1
)
=
2
+
7
−
18
f(-1) = 2 + 7 - 18
f
(
−
1
)
=
2
+
7
−
18
.
Subtract
18
18
18
from
9
9
9
:
Calculate the final value:
f
(
−
1
)
=
9
−
18
f(-1) = 9 - 18
f
(
−
1
)
=
9
−
18
.
Subtract
18
18
18
from
9
9
9
:
Calculate the final value:
f
(
−
1
)
=
9
−
18
f(-1) = 9 - 18
f
(
−
1
)
=
9
−
18
. Subtract
18
18
18
from
9
9
9
:
f
(
−
1
)
=
−
9
f(-1) = -9
f
(
−
1
)
=
−
9
.
More problems from Evaluate expression when a complex numbers and a variable term is given
Question
Simplify.
\newline
8
i
+
6
i
8i + 6i
8
i
+
6
i
\newline
\newline
Write your answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Find the complex conjugate of the given number.
\newline
4
+
10
i
4 + 10i
4
+
10
i
\newline
\newline
Write your answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Simplify.
\newline
−
4
i
−
9
i
\frac{{-4i}}{{-9i}}
−
9
i
−
4
i
\newline
\newline
Write your simplified answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Combine the like terms to create an equivalent expression.
\newline
7
k
−
k
+
19
=
0
7k-k+19=\boxed{\phantom{0}}
7
k
−
k
+
19
=
0
Get tutor help
Posted 1 year ago
Question
Apply the distributive property to factor out the greatest common factor.
\newline
9
+
12
n
=
9+12 n=
9
+
12
n
=
Get tutor help
Posted 9 months ago
Question
Solve the equation.
\newline
12
=
n
−
9
n
=
□
\begin{aligned} & 12=n-9 \\ n= & \square \end{aligned}
n
=
12
=
n
−
9
□
Get tutor help
Posted 1 year ago
Question
What is the amplitude of
y
=
−
sin
(
8
x
−
3
)
+
5
y=-\sin (8 x-3)+5
y
=
−
sin
(
8
x
−
3
)
+
5
?
\newline
units
Get tutor help
Posted 1 year ago
Question
What is the period of
\newline
y
=
4
sin
(
−
2
x
+
7
)
−
1
?
y=4 \sin (-2 x+7)-1 \text { ? }
y
=
4
sin
(
−
2
x
+
7
)
−
1
?
\newline
Give an exact value.
\newline
units
Get tutor help
Posted 1 year ago
Question
3
⋅
(
3
+
20
i
)
=
3 \cdot(3+20 i)=
3
⋅
(
3
+
20
i
)
=
\newline
Your answer should be a complex number in the form
a
+
b
i
a+b i
a
+
bi
where
a
a
a
and
b
b
b
are real numbers.
Get tutor help
Posted 1 year ago
Question
(
35
−
23
i
)
+
(
13
+
25
i
)
=
(35-23 i)+(13+25 i)=
(
35
−
23
i
)
+
(
13
+
25
i
)
=
\newline
Express your answer in the form
(
a
+
b
i
)
(a+b i)
(
a
+
bi
)
.
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant